Charge fluctuation, charge ordering, and zero-gap state in organic conductors - Takahashi, Toshihiro (Physica. B, Condensed matter, 2012)
We have carried out a series of measurements of angular dependence of solid-state NMR spectrum using single crystal samples on various organic molecular conductors, in order to investigate the natures of the electronic states at low temperatures. We confirmed a charge ordered insulating state in α-(BEDT-TTF)2I3 and large charge disproportionation in the metallic state of this salt. In another charge ordered system, θ-(BEDT-TTF)2RbZn(SCN)4, we observed unusual NMR line broadening, proportional to resonance shift, in the metallic state above the transition. We found that this broadening is due to charge disproportionation, or more correctly, due to the inhomogeneity of local susceptibility at nuclear sites and analyzed its dynamics. We observed similar broadening in various organic molecular conductors as well, such as θ-(BEDT-TTF)2CsZn(SCN)4, an exotic Bechgaad salt, (TMTSF)2FSO3, and λ-type BETS salts, λ-(BETS)2(Fe,Ga)Cl4. We found the mechanism of CD in each system is different, respectively.